Photodegradation of ethylene/propylene/polar monomers co- and terpolymers. I - Prepared by group 4 catalyst systems - Fernandes, Susete N.; Correia, Sandra; Prasad, A. V.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Marques, Maria M.; Singh, R. P. (Journal of Macromolecular Science-Pure and Applied Chemistry, 2005)
The photooxidative degradation behavior of polyethylene, its copolymers (propylene/polar monomers) and terpolymers, synthesized by a group 4 catalyst system, has been studied by Fourier transform infrared spectroscopy and confirmed with scanning elecrton microscopy for morphological changes. The kinetics of photodegradation has also been studied. Surface damage caused by polychromatic (>= 290 nm) at 55 degrees C in air is presented in different micrographs. The rate of photodegradation is very fast in terpolymers containing polar monomers as compared with copolymers and polyethylene. Morphological study of these photodegraded samples showed a very good relation with photodegradation results.
Keywords: functional polyolefins; Photodegradation; UV irradiation